Pharmacogenetics of cardiovascular drugs - Pajović, Vladislav; Žigon, Nina (Medicinski podmladak, 2023)
Individual variations in the patient’s response to the administered drugs are a frequent and important clinical problem in medicine and pharmacology. It is especially important to consider these issues when counting cardiovascular disease (CVD) treatment, since CVD are characterised by high incidence in the population, making cardiovascular drugs the most prescribed medication. Currently used medical therapies are adapted to best fit the needs of a wide population of patients who can benefit from it, despite the fact that a certain number of individuals will suffer from inadequate therapeutic effects or even intoxication. By examining the genetic basis that causes individual variations in the response to drugs, pharmacogenetics enables the personalisation of drug therapy, with the aim to identify patients who are exposed to an increased risk of serious drug side effects and those missing the maximum drug effectiveness. Polymorphism of genes that encode protein units of enzymes involved in the drug metabolism, mainly cytochrome P450 enzymes, receptors and drug transporters, affect both pharmacokinetics and pharmacodynamics of drugs often prescribed for CVD, such as beta blockers, ACE inhibitors, warfarin, clopidogrel and statins. This approach in cardiological practice would enable adjusting the therapy for patients based on gene polymorphisms, by changing the dose of the existing drugs or using another drug of choice. Although including pharmacogenetics in daily clinical practice would bring along large diagnostic costs, as well as potential legal and ethical dilemmas, a substantial number of patients, overall society and the health system in general could benefit from enhanced therapeutic effects as well as decreased side effects of the applied therapy.